Forest Dynamics and Disturbance Regimes : Studies from Temperate Evergreen-Deciduous Forests - Frelich, Lee E., 1957- (Cambridge studies in ecology., 2002)
"More than a quarter of the world's forests lie within the cool-to-cold temperate zones of the northern and southern hemisphere. Their distinctive mosaics of evergreen conifers and deciduous hardwood species have been shaped by fire, wind and herbivory over thousands of years. In the last few centuries human activities have increasingly changed the dynamics of these mosaics: fire suppression and exclusion have reduced fire frequency, harvesting and grazing have increased, and a changing climate may be leading to a change in the frequency of high winds. While the exact influence of these changes remains to be determined, this book provides a major contribution to the study of forest dynamics by considering three important themes: The combined influence of the three main disturbance types--wind, fire and herbivory--on the successional trajectories and structural characteristics of forests; The interaction of deciduous and evergreen tree species to form various mosaics which, in turn, differentially influence the environment and disturbance regime; The significance of temporal and spatial scale with regard to the overall impact of disturbances. These themes are explored via case studies from the forests in the Lake States of the USA (Minnesota, Wisconsin and Michigan) where the presence of large primary forest remnants presents a unique opportunity to study and compare the long-term dynamics of near-boreal, pine and hemlock-hardwood forests. The comparability of these forests to forests in other cool-to-cold temperate zones allows generalizations to be made that may apply more widely."--Publisher's description